Selection of High Oil Yielding Trees of Millettia pinnata (L.) Panigrahi, Vegetative Propagation and Growth in the Field - Ni Luh Arpiwi; I Made Sutha Negara; I Nengah Simpen (Journal of Tropical Life Science, 2017)
Millettia pinnata (L.) Panigrahi is a potential legume tree that produces seed oil for biodiesel feedstock. The initial step for raising a large-scale plantation of the species is selection of high oil yielding trees from the natural habitat. This is followed by vegetative propagation of the selected trees and then testing the growth of the clone in the field. The aim of the present study was to select high-oil yielding trees of M. pinnata, to propagate the selected trees by budding and to evaluate the survival and growth of budded plants in the field. Pods were collected from 30 trees in Lovina Beach, Buleleng Regency, Bali. Oil was extracted from seeds using soxhlet with hexane as a solvent. The high oil yielding trees were propagated by budding using root stocks grown from M. pinnata seeds. Scions were taken from young branches of selected trees. Incision was made on rootstock and the same size of cut was made on a scion containing a single bud. The scion was inserted to the incision of rootstock then closed tightly using plastic strips. The plastic was removed when the scion grew into a little green shoot. One month after plastic removal, the scion union grew into a single shoot and then the budded plants were removed to polybags. Budded plants were planted in the field of Bukit Jimbaran, Badung Regency, Bali with 4 × 4 spacing. Results showed all budded plants successfully grow new shoots. Two months after planting the survival of budded plants was 100%. Plant height increased by 22.13 cm, stem diameter increased by 2.43 mm and the number of compound leaf increased by 2.08. It can be concluded that four high oil yielding trees were selected from Lovina Beach and successfully propagated by budding. Survival of budded plants was 100% with vigorous growth.